1996
DOI: 10.1016/s0928-8244(96)00071-5
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry and cell biology of bacterial endotoxins

Abstract: and multi-organ failure. The resulting septic shock syndrome has a mortality rate of 20-50% and causes approximately 100,000 deaths annually in the USA [5]. On the other hand, low doses of LPS are thought to be beneficial for the host, e.g. by causing immunostimulation and enhanced resistance to infections and malignancy [6]. The harmful as well as the beneficial host responses to LPS are mediated by endogenous mediators, cytokines, which are released by various cells, e.g. monocytes/macrophages, vascular cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 35 publications
1
74
0
Order By: Relevance
“…The small amount of data concerning the activities of LPS in plants or in plant cell cultures is in contrast to numerous reports about enterobacterial LPS and their interaction with components of the innate immune system (Schletter et al 1995;Holst et al 1996). Further studies will show to what extent the role of LPS in pathogen recognition is similar in animals and plants.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The small amount of data concerning the activities of LPS in plants or in plant cell cultures is in contrast to numerous reports about enterobacterial LPS and their interaction with components of the innate immune system (Schletter et al 1995;Holst et al 1996). Further studies will show to what extent the role of LPS in pathogen recognition is similar in animals and plants.…”
Section: Discussionmentioning
confidence: 82%
“…The outstanding role of endotoxins (LPS) in the induction of defence responses in cells of the immune system (Holst et al 1996) led us to the question of whether the LPS of the phytopathogen Xanthomonas campestris is Fig. 4A, B Induction of a refractory state in tobacco cell cultures following a pre-incubation with YE or LPS Xcc .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After peripheral nerve injury, Schwann cells have been reported to produce TNF-α (Wagner and Myers 1996). LPS has been reported to cause hyperalgesia (Watkins et al 1994(Watkins et al , 1995Reeve et al 2000), is known to enhance not only TNF-α synthesis and release (Holst et al 1996) but also the expression of TNFR2 and, to a lesser extent, of TNFR1 (Nadeau and Rivest 1999). Li et al (2004) showed that LPS induced expression of TNF-α in rat DRG exclusively in non-neuronal cells, but in sciatic nerve, its expression pattern is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, H. magadiensis displayed acyloxacyl derivatives for both 2′ and 3′ positions of GlcNII, whereas H. pantelleriensis displayed only acyloxacyl for 2′ position of the same residue. The biological activity of lipid A strongly depends on its primary structure, especially the fatty acid composition and distribution (Holst et al 1996;Seydel et al 2000). As the lipid A of H. magadiensis displayed a strong antagonist activity (Ialenti et al 2006), it will be very interesting to observe the biological activity of the lipid A from H. pantelleriensis strain to check if there are any structure-activity relationships.…”
Section: Mass Spectrometry Analysismentioning
confidence: 99%